Management of Pharmaceutical Preparations in the Form of Drugs at Surya Melati Muhammadiyah Hospital - Indasah; Fitdhiar Wira Qalbi; Sentot Imam Suprapto (Universitas STRADA Indonesia, 2025)
Drug management in hospitals covers four essential stages: selection, planning and procurement, distribution, and use. This study aimed to evaluate the drug management system at Surya Melati Muhammadiyah Hospital. A qualitative phenomenological approach was used, involving 17 informants selected purposively from pharmacy staff, medical professionals, warehouse officers, and finance personnel. Data were obtained through document review and in-depth interviews, then analyzed by comparing findings with existing standards. The results show that the drug selection process has generally aligned with hospital needs, although prescription adherence to the formulary remains low.